Some Recent Developments in Adaptive Tuned Vibration Absorbers/Neutralisers - Michael J. Brennan (Shock and Vibration)
The vibration absorber has been used for vibration control purposes in many sectors of engineering from aerospace, to automotive to civil, for the past 100 years or so. A limitation of the device, however, is that it acts like a notch filter, only being effective over a narrow band of frequencies. Recent developments have overcome this limitation by making it possible to tune the device over a range of frequencies. This has been achieved by incorporating a variable stiffness element that can be adjusted in real-time. In this paper, some ways in which stiffness change can be achieved in practice are reviewed and some examples of prototype adaptive tuned vibration absorbers (ATVAs) are described. A simple control scheme to automatically tune an ATVA is also presented.